Pengaruh Jenis dan Pola Konsumsi Makanan yang Mengandung Vitamin D Terkait Gangguan Fungsi Paru pada Tukang Bangunan: Effect of Types and Food Consumption Patterns that Contain Vitamin D Related to Pulmonary Disorders in Builders - Erlin Oktavia; Amelia Lorensia; Rivan Virlando Suryadinata (Jurnal Sains dan Kesehatan, 2023)
Respiratory disorders are a major cause of morbidity and mortality. In addition to pollution from vehicles, pollution from work such as building work, demolition, excavation can also cause respiratory problems. Vitamin D deficiency is the opposite of respiratory disease, with effects on respiratory infections and lung function. This study discusses the consumption patterns of foods containing vitamin D against lung function disorders in construction workers. This research is a retrospective study by collecting respondents using purposive sampling. Variables to be added: food intake containing vitamin D with the Food Frequency Questionnaire (FFQ) method, pulmonary function using the spirometry. In this study there were 118 respondents consisting of 58 respondents with pulmonary function disorders and 60 respondents without pulmonary function disorders. Of the 58 respondents who had a malfunctioning, there were 14 respondents (24.14%) who experienced a deficit in food intake containing vitamin D and 44 respondents (75.86%) enough food intake containing vitamin D. Of the 60 respondents who did not have functional problems pulmonary, 16 respondents (26.67%) needed to increase the food intake deficit that contained vitamin D and 44 respondents (73.33%) provided enough food containing vitamin D. The most commonly consumed foods were the second group containing eggs and catfish. The results of the different tests showed the results of a P value of 0.752 which means there was no difference between the intake of foods containing vitamin D between the two groups. The pattern of consumption of foods containing vitamin D does not affect the occurrence of lung function disorders in builders. Keywords:          Food intake, vitamin D, lung function   Abstrak Gangguan pernafasan merupakan penyebab utama morbiditas dan mortalitas. Selain pencemaran dari kendaraan, pencemaran dari pekerjaan seperti pekerjaan gedung, pembongkaran, penggalian juga dapat menyebabkan gangguan pernafasan. Kekurangan vitamin D adalah kebalikan dari penyakit pernafasan, dengan efek pada infeksi pernafasan dan fungsi paru-paru. Penelitian ini membahas tentang pola konsumsi makanan yang mengandung vitamin D terhadap gangguan fungsi paru pada pekerja bangunan. Penelitian ini merupakan penelitian retrospektif dengan pengambilan responden menggunakan purposive sampling. Variabel yang ditambahkan: asupan makanan yang mengandung vitamin D dengan metode Food Frequency Questionnaire (FFQ), fungsi paru menggunakan spirometri. Dalam penelitian ini terdapat 118 responden yang terdiri dari 58 responden dengan gangguan fungsi paru dan 60 responden tanpa gangguan fungsi paru. Dari 58 responden yang mengalami malfungsi terdapat 14 responden (24,14%) yang mengalami defisit asupan makanan yang mengandung vitamin D dan 44 responden (75,86%) yang cukup asupan makanan yang mengandung vitamin D. Dari 60 responden yang tidak berfungsi Masalah paru, 16 responden (26,67%) perlu meningkatkan defisit asupan makanan yang mengandung vitamin D dan 44 responden (73,33%) menyediakan makanan yang cukup mengandung vitamin D. Makanan yang paling banyak dikonsumsi adalah kelompok kedua yang mengandung telur dan ikan lele. Hasil uji beda menunjukkan hasil nilai P sebesar 0,752 yang berarti tidak ada perbedaan asupan makanan yang mengandung vitamin D antara kedua kelompok. Pola konsumsi makanan yang mengandung vitamin D tidak mempengaruhi terjadinya gangguan fungsi paru pada tukang bangunan. Kata Kunci:         Asupan makanan, vitamin D, fungsi paru-paru